The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.48550/arxiv.1912.00182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spin Solitons in Spin-1 Bose-Einstein Condensates

Abstract: Solitons in multi-component Bose-Einstein condensates have been paid much attention, due to the stability and wide applications of them. The exact soliton solutions are usually obtained for integrable models. In this paper, we present four families of exact spin soliton solutions for nonintegrable cases in spin-1 Bose-Einstein Condensates. The whole particle density is uniform for the spin solitons, which is in sharp contrast to the previously reported solitons of integrable models. The spectrum stability anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
(189 reference statements)
0
2
0
Order By: Relevance
“…As a first step one can consider quenches between the first and second order phase transition boundaries to investigate how the relevant in each phase spin-1 soliton solutions migrate or transform from one phase to the other. Yet another interesting perspective would be to study interactions [22,43,50] between the spinor solitons identified within each phase of the above-obtained phase diagram or even unravel lattices consisting of multiple DBB, DDB and DDD spinorial solitons in analogy to the two-component settings e.g. of Refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a first step one can consider quenches between the first and second order phase transition boundaries to investigate how the relevant in each phase spin-1 soliton solutions migrate or transform from one phase to the other. Yet another interesting perspective would be to study interactions [22,43,50] between the spinor solitons identified within each phase of the above-obtained phase diagram or even unravel lattices consisting of multiple DBB, DDB and DDD spinorial solitons in analogy to the two-component settings e.g. of Refs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, owing to the far richer phase diagram exhibited by such gases [36] (see, also, [37] for a recent discussion and [38] for the impact of many-body effects) already several works have been devoted in studying a variety of nonlinear excitations that arise in them [39][40][41][42][43][44]. These include for instance spin domains [45,46], spin textures [47,48], the very recently experimentally observed dark-dark-bright (DDB) and dark-bright-bright (DBB) solitons [49] (and variants [50], as well as interactions [22] thereof) and even twisted magnetic solitons [51].…”
Section: Introductionmentioning
confidence: 99%